Ausstieg aus dem Bild : Im Blickfeld - Jahrbuch der Hamburger Kunsthalle - Meyer, Franz; Schmidt-Wulffen, Stephan; von Graevenitz, Antje; Pascheit, Olaf; Bippus, Elke; Pilgram, Markus; Hedinger, Bärbel; Germer, Stefan; Herding, Klaus; Döring, Jürgen; Brassat, Wolfgang; Ketelsen, Thomas; et al. (Hamburg : Christians Verlag, 1997)
Beuys, Joseph ; Serra, Richard ; Darboven, Hanne ; Buren, Daniel ; Slominski, Andreas ; Van Gogh, Vicent ; etc.
Duits
boek